Beyond grammar: religious and cultural awareness in language communication - Abdul Manaf, Nor Faridah (The Islamic Academy, Cambridge, 2005)
This paper looks at the necessity that the world today goes beyond the technical framework that we look up to as symbols of civilization, material development and advancement.